PENGGUNAAN USER PERSONA UNTUK EVALUASI DAN MENINGKATKAN EKSPEKTASI PENGGUNA DALAM KEBUTUHAN SISTEM INFORMASI AKADEMIK - Kharisma Muzaki Ghufron; Wahyu Andhyka Kusuma; Fauzan Fauzan (SINTECH (Science and Information Technology) Journal, 2020)
Human-Computer Interaction (HCI) is a scientific field to determine user characteristics or so-called persona. HCI describes a system that must be easy to use, provides security to users, easy to learn and has usability. The purpose of the study was conducted to obtain various perspectives on the use of software in the InfoKHS University of Muhammadiyah Malang (UMM) academic system according to user characteristics so that the design of software requirements is expected to be representative of various types of users. The HCI assessment is carried out in software development (SD) focusing on the elicitation of needs. Focus on using user methods. As an analysis of user needs. Qualitative data were analyzed based on country hypotheses obtained for the first time in this research phase. In this study, a User Persona was done with an iterative method to ensure each phase was validated. The results show that iterations are needed several times to get the use of detailed cases diagram of each user's needs.